2018
DOI: 10.1016/j.ibror.2018.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation of corticotropin-releasing hormone gene in stress response

Abstract: As a central player of the hypothalamic-pituitary-adrenal (HPA) axis, the corticotropin -releasing hormone (CRH) neurons in the hypothalamic paraventricular nucleus (PVN) determine the state of HPA axis and play a key role in stress response. Evidence supports that during stress response the transcription and expression of CRH was finely tuned, which involved cis-element-transcriptional factor (TF) interactions and epigenetic mechanisms. Here we reviewed recent progress in CRH transcription regulation from DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 138 publications
0
16
0
Order By: Relevance
“…Previous studies have shown that a group of parvocellular neuroendocrine cells (PNCs) of the hypothalamic–pituitary–adrenal (HPA) axis the HPA axis, through somatic cells production and released into capillaries entering pituitary portal circulation, directly control pituitary corticotroph function, and downstream glucocorticoid secretion by the adrenal glands, of which most widely studied is CRH (Wamsteeker Cusulin et al, 2013). CRH has a major role in the regulation of the HPA axis, and it is the chief organizer of the body’s response to stress (Wang et al, 2011, 2013; Yang et al, 2015; Fang et al, 2016; Peng et al, 2017; Zhou and Fang, 2018). The anatomical distribution of CRH in the brain that this peptide is not only a key regulator of neuroendocrine stress, but also regulates neuronal activity in a neuromodulated manner (Dedic et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that a group of parvocellular neuroendocrine cells (PNCs) of the hypothalamic–pituitary–adrenal (HPA) axis the HPA axis, through somatic cells production and released into capillaries entering pituitary portal circulation, directly control pituitary corticotroph function, and downstream glucocorticoid secretion by the adrenal glands, of which most widely studied is CRH (Wamsteeker Cusulin et al, 2013). CRH has a major role in the regulation of the HPA axis, and it is the chief organizer of the body’s response to stress (Wang et al, 2011, 2013; Yang et al, 2015; Fang et al, 2016; Peng et al, 2017; Zhou and Fang, 2018). The anatomical distribution of CRH in the brain that this peptide is not only a key regulator of neuroendocrine stress, but also regulates neuronal activity in a neuromodulated manner (Dedic et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…The CRH gene encodes a member of the corticotropin-releasing hormone family and is mainly expressed by the hypothalamic paraventricular nucleus and secreted into the hypophyseal portal system [47]. It plays a crucial role in eliciting the stress response through stimulation of the hypothalamic, pituitary, adrenal axis and the secretion of cortisol in response to noxious stimulation [48].…”
Section: Discussionmentioning
confidence: 99%
“…et al observed no significant difference in total testosterone, LH, or FSH with isotretinoin therapy [23]. Similarly, Marynick et al found no statistically significant changes in serum DHEAS, total testosterone, LH, or FSH with isotretinoin therapy [24].…”
Section: Discussionmentioning
confidence: 99%